PENGARUH SUHU DAN LAMA PENYEDUHAN TERHADAP AKTIVITAS ANTIOKSIDAN DAN SIFAT SENSORIS TEH HERBAL DAUN ALPUKAT (Persea americana Mill.) - Dewata, I Putu; Ari Sandhi W, Putu; Rai Widarta, I Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
Avocado leave (Persea americana Mill) is one from nature that can be used as herbal tea. This research aimed to acknowledge the temperature and the length of brewing effect on antioxidants reaction and sensory properties of the avocado leave herbal tea, with the best charateristics. This research applied Completely Randomized Design (Rancangan Acak Lengkap/ RAL) with two factors factorial pattern, which were three levels of the water temperature; 70oC, 85oC, 100oC and three different length of brewing times, which were 1 minute, 3 minutes and 5 minutes. The experiment was done two times and there were 18 unit of experiments were done in total. The data taken from the experiment were analyzed with variance and the experiment was continued with DMRT test. The results show that the temperature and length of brewing affect highly on total phenol, flavonoid, antioxidants activity, and sensory properties of the avocado leave herbal tea. The best result is the experiment with 100oC water temperature in 5 minutes of brewing that produce total phenol 291,63mg/100g, total flavonoid 16,71mg/g, antioxidants reaction 18,55% and green brown sensory properties, specific avocado leave herbal tea smell, a bit bitter, and overall beloved result.